2021
DOI: 10.1177/1753495x211011910
|View full text |Cite
|
Sign up to set email alerts
|

Childhood adversity, prenatal depression, and maternal inflammation across pregnancy

Abstract: Background To examine whether change in neutrophil–lymphocyte ratio, a marker of systemic inflammation, differs by childhood adversity and prenatal depression. Methods Prenatal complete blood count data were used to calculate neutrophil–lymphocyte ratio in first and third trimesters. The Adverse Childhood Experiences scale measured childhood adversity, and the Patient Health Questionnaire-9 measured depression. This is a secondary analysis of a study of predictors of risk for sleep-disordered breathing. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
2
2
0
Order By: Relevance
“…As a matter of fact, NLR is signi cantly higher in patients with AN and a history of CM compared to patients with AN without history of CM. This nding is in line to what has been recently demonstrated during pregnancy in women who have experienced childhood sexual abuse [35]. In this last study, NLR was signi cantly higher in pregnant women with a history of childhood sexual abuse independently from prenatal depression [35].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As a matter of fact, NLR is signi cantly higher in patients with AN and a history of CM compared to patients with AN without history of CM. This nding is in line to what has been recently demonstrated during pregnancy in women who have experienced childhood sexual abuse [35]. In this last study, NLR was signi cantly higher in pregnant women with a history of childhood sexual abuse independently from prenatal depression [35].…”
Section: Discussionsupporting
confidence: 92%
“…This nding is in line to what has been recently demonstrated during pregnancy in women who have experienced childhood sexual abuse [35]. In this last study, NLR was signi cantly higher in pregnant women with a history of childhood sexual abuse independently from prenatal depression [35]. The current medical literature points towards a role of epigenetics via DNA methylation on the HPA axis dysregulation and immune system activation after CM [36].…”
Section: Discussionsupporting
confidence: 89%
“…Given the role of SEA in modulating inflammatory and pain processes as well as in regulating glucocorticoid secretion, lowered SEA levels in the hair of pregnant women with a CM history may implicate that CM contributes to an aberrant immune and HPA axis (re-)activity in late pregnancy through altered SEA regulation. Indeed, there is evidence that women with CM history exhibit higher inflammatory activity during pregnancy (Boeck et al, 2016 ; Bublitz, De La Monte, Martin, Larson, & Bourjeily, 2017 , 2022 ; Kleih et al, 2022 ). NAEs are known to inhibit inflammation by binding to peroxisome proliferator-activated-receptors (PPAR) (O'Sullivan & Kendall, 2010 ), and therefore a reduced SEA signaling may contribute to increased inflammation in pregnant women with a history of CM.…”
Section: Discussionmentioning
confidence: 99%
“…no abuse). Finally, Bublitz et al [35] showed that a CSA history was linked to a greater change in the Neutrophil-lymphocyte ratio (NLR, a measure of systematic inflammation) over pregnancy.…”
Section: Biomedical Risksmentioning
confidence: 99%